Effectiveness of continuity of care in postoperative patients with cervical cancer: a systematic evaluation and meta-analysis of a randomized controlled trial - Fu, Wenfeng; Xu, Qiannan; Lu, Haizhen; Yang, Yuanyuan; Zheng, Yanxue (Frontiers in Oncology, 2024)
ObjectiveTo analyze the effect of implementing continuity of care for postoperative patients with cervical cancer, to improve the continuity of care model in China, and to provide comprehensive, continuous, and personalized care services for patients.MethodsPubMed, Web of Science, Science Direct, China Knowledge Network, Wanfang database, China Biomedical sources Service System, Wipro, Cochrane Library, Embase, and other databases were searched for relevant sources on the effect of continuity of care on postoperative cervical cancer patients. The Cochrane Handbook of Systematic Evaluation and Revman 5.3 software was used to evaluate the quality of the retrieved sources and perform meta-analysis.ResultsCompared with the control group, extended care could improve patients’ quality of life [SMD=1.35,95%CI(1.05,1.64), P<0.05], alleviate patients’ postoperative anxiety [SMD=-0.92,95%CI(-1.85,0.00), P<0.05] and postoperative depression [SMD=-1.15,95% CI(-1.35,-0.95), P<0.05].ConclusionThe use of continuity of care form has an important role in improving the quality of life of cervical cancer patients and improving negative emotions.